Efficacy of personal symptom and family history questionnaires when screening for inherited cardiac pathologies: the role of electrocardiography. Issue 3 (23rd August 2007) - Wilson, M G; Basavarajaiah, S; Whyte, G P; Cox, S; Loosemore, M; Sharma, S
Abstract : Aims: This study sought to confirm the efficacy of using resting 12-lead ECG alongside personal symptom and family history questionnaires and physical examination when screening for diseases with the potential to cause sudden cardiac death in the young. Methods and results: 1074 national and international junior athletes (mean age 15.8 (SD 0.7) years, range 10 to 27) and 1646 physically active schoolchildren (16.1 (SD 2.1) years, range 14 to 20) were screened using personal and family history questionnaires, physical examination and resting 12-lead ECG. Nine participants with a positive diagnosis of a disease associated with sudden cardiac death were identified. None of the participants diagnosed with a disease associated with sudden cardiac death were symptomatic or had a family history of note. Conclusion: : Family history and personal symptom questionnaires alone are inadequate to identify people with diseases associated with sudden cardiac death. Use of the 12-lead ECG is essential when screening for cardiac pathology in the young.